2011
DOI: 10.22401/jnus.14.4.20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antimicrobial Susceptibility of Pathogens in Urinary Tract Infections

Abstract: This study was done to assess the bacterial profile and antibiotic susceptibility pattern of urinary tract infections (UTIs) pathogens. For proper identification of causative microbial agents, mid stream urine samples from 459 patients with clinical symptoms suspected to be UTI were collected, cultured and subjected to appropriate biochemical tests. These samples were collected from Teaching Laboratories Center in Baghdad during the study period (1 st January 2009-1 st July 2009). The antimicrobial sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…The overall males to females ratio were (1:14). This fi nding was consistent with other reported studies from many parts of the world showing a statistically predominance of females [16][17][18][19]. This is usually related to the anatomical and pathogenic factors of females [20].…”
Section: Resultssupporting
confidence: 93%
“…The overall males to females ratio were (1:14). This fi nding was consistent with other reported studies from many parts of the world showing a statistically predominance of females [16][17][18][19]. This is usually related to the anatomical and pathogenic factors of females [20].…”
Section: Resultssupporting
confidence: 93%
“…in the study. Whereas, a studies showed that the second most common uropathogen in Baghdad and Tikrit were Enterobacter spp and Proteus mirabilis respectively (Mahmood, 2011;Al-Jebouri and Mdish, 2013). In this study, the predominance incidence of infection was in females (73.3%).…”
Section: Discussionmentioning
confidence: 99%
“…A major worldwide problem nowadays is the resistance of the invading microorganisms to the treatment; resistant organisms have emerged due to several factors related to the genetic nature of the organisms and selective antimicrobial pressure in humans (Saffar et al, 2008;Habeeb et al, 2014;Hussein et al, 2017). Globally UTIs area serious health problem which affects millions of peoples every year (Mahmood, 2011).Worldwide, UTI is identified in about 150 million people annually (Gupta et al, 2001). About 40% of all hospital acquired infections are due to UTIs which are catheter associated (Ruden et al, 1997).About 25% of patients who subjected to urinary catheter for one week or more developed bacteriuria with a daily risk of 5-7% (Maki and Tambyah, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…About 10.8 million patients in United States visited an emergency development for treatment of UTI (Sammon et al, 2014). Bacterial organisms which cause UTI may involve Escherichia coli, Klepsiella, Pseudomonas, Proteus mirabilis and Enterococcus fecalis (Mahmood, 2011;Dromigny, 2005).…”
Section: Introductionmentioning
confidence: 99%